3D reconstitution of nerve–blood vessel networks using skeletal muscle-derived multipotent stem cell sheet pellets. (July 2013) - Tamaki, Tetsuro; Soeda, Shuichi; Hashimoto, Hiroyuki; Saito, Kosuke; Sakai, Akihiro; Nakajima, Nobuyuki; Masuda, Maki; Fukunishi, Nahoko; Uchiyama, Yoshiyasu; Terachi, Toshiro; Mochida, Joji
Aim: To cover the large tissue deficits associated with significant loss of function following surgery, a 3D gel-patch-like nerve–vascular reconstitution system was developed using the skeletal muscle-derived multipotent stem cell (Sk-MSC) sheet pellet.Materials & methods: The Sk-MSC sheet pellet was prepared from GFP transgenic mice by the collagenase extraction and 7 days expansion cell culture, and transplanted into a severe muscle damage model with large disruptions to muscle fibers, blood vessels and peripheral nerves.Results: At 4 weeks after transplantation, engrafted cells contributed to nerve–vascular regeneration associated with cellular differentiation into Schwann cells, perineurial/endoneurial cells, vascular endothelial cells and pericytes. However, skeletal myogenic differentiation was scarcely observed. Paracrine effects regarding donor cells/tissues could also be expected, because of the active expression of neurogenic and vasculogenic factor mRNAs in the sheet pellet.Conclusion: These results indicate that the vigorous skeletal myogenic potential of Sk-MSCs was clearly reduced in the sheet pellet preparation and this method may be a useful adjuvant for nerve–vascular regeneration in various tissue engineering applications.